A method for estimating liner shipping time under uncertainty. (17th April 2019) - Lin, Min; Li, Miao; Hao, Hao; Zhen, Lu
With the rapid development of container transportation and the fierce competition among ports, container terminal operators pay more attention to meet the individual needs of customers. This study develops a system to estimate container liner shipping arrival time and the probability distribution for each time set by considering transit process and the periodicity of liner shipping. This system can give the most possible arrival time of cargoes to customers in advance, and then improve the level of port services. Also, a recursive algorithm based solution method and a parallel computing based solution method are proposed for solving the problem. Computational test is conducted on different scales and the results show the effectiveness of the proposed solution approach.